Activities That May Influence the Risk of Crocodile (Crocodylus Acutus: Reptilia: Crocodilidae) Attack to Humans in the Tempisque River Area, Guanacaste, Costa Rica. - Sandoval-Hernández, Iván (2017)
One of the largest populations of crocodiles in Costa Rica is located at the Tempisque River. The species is threatened by habitat loss and poaching; but its populations have grown due to the protection given by law. The research was conducted in Guanacaste, Costa Rica. We made a characterization of popular knowledge, activities and perceptions of 374 residents of the study area. It was found that 55% believe that the crocodiles are abundant, 70% believe that populations have increased. The most dangerous activities done are recreation, swimming and fishing. There are significant differences between the proportions of response (X2: 71, n = 10, p <0.0001 X2). These activities are done daily (25%), weekly (30%), monthly (18%) and annually (10%). The risk of attack and the crocodile’s density in the river are not recognized. Also, a lack of knowledge about the natural history and ecology of the species is shown. The reasons for attacks are: the aggressiveness of the animals and their density. There are differences in the responses on the reasons of the attacks (X2: 35, n 8 p <0.0001). Generally, the crocodile perception is unfavorable.